2017
DOI: 10.1002/pc.24610
|View full text |Cite
|
Sign up to set email alerts
|

Processing, characterization, and parametric analysis of erosion behavior of epoxy‐LD sludge composites using Taguchi technique and response surface method

Abstract: Linz‐Donawitz sludge (LDS) are the microsized solid particles that are recovered after wet cleaning of the gas emerging from basic oxygen furnace during steel making. This article reports on the development of a new class of thermoset polymer composites filled with this industrial waste called LDS. It includes processing, characterization and solid particle erosion wear of epoxy composites filled with different proportions (0, 5, 10, 15, and 20 wt%) of LDS by solution casting technique. The solid particle eros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…This trend in erosive wear rate for all the composites can be explained according to the area of erodent impact on the target surface. Many studies demonstrated striking area generated by erodent particles impacting a target surface remain maximum at 60° . Any deviation in impingement angle will results in lowering the striking area of erodent.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This trend in erosive wear rate for all the composites can be explained according to the area of erodent impact on the target surface. Many studies demonstrated striking area generated by erodent particles impacting a target surface remain maximum at 60° . Any deviation in impingement angle will results in lowering the striking area of erodent.…”
Section: Resultssupporting
confidence: 94%
“…Lower striking area means reduced surface deformation and hence reduced erosive wear rate. Similar results were reported by Prakash et al and A. Purohit and A. Satapathy where maximum erosive wear rate was observed at 60° of impingement angle indicating semi‐brittle erosion behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed that LD slag content is a significant control factor for minimizing the erosion rate of the produced composites. Numerous publications of Purohit and Satapathy studied the influence of LD slag, LD sludge and BF slag on the sliding wear and erosion wear of the composites based on epoxy resin matrix [ 72 , 73 , 74 , 75 ]. The obtained results indicated that with increasing content of filler, both erosion wear- and sliding wear resistance of the composites increases.…”
Section: Industrial Waste Materialsmentioning
confidence: 99%
“…Property map to compare the erosion rate of E0, EC‐10, EC‐20 and EC‐30 samples at various angles of impingement (30, 45, 60 and 90°) with the existing studies is presented in Figure 13 11,17,45,47,53,56–61 . Results obtained from present study and data extracted from existing literature are mapped with respect to density of the samples.…”
Section: Property Mapmentioning
confidence: 99%